2014
DOI: 10.1016/j.corsci.2014.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Applications of scanning electrochemical microscopy (SECM) for local characterization of AZ31 surface during corrosion in a buffered media

Abstract: Different modes of scanning electrochemical mapping (SECM) such as surface generation/tip collection (SG/TC), amperometry, AC-SECM and potentiometry were employed to characterize the active/passive domains, hydrogen gas (H2) evolution and local pH on a corroding surface of AZ31 in simulated biological fluid (SBF). It was found that the main domains of H2 evolution are associated with lower insulating properties of the surface as well as higher local pH. The near surface pH was found to be highly alkaline indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
62
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 49 publications
1
62
0
2
Order By: Relevance
“…In generation/collection (G/C) mode of SECM, electrochemically oxidisable or reducible species produced at the substrate can be sensed via an electrochemical reaction at the SECM probe. Applying an oxidative potential at the SECM, flux of H 2 evolution can be sensed and implemented to evaluate corrosion behaviour on Mg surface with a localized approach [13][14][15]. In comparison to other well-trusted corrosion measurement methods such as weight loss measurement and hydrogen collection [16,17], SECM presents the unique capability of studying spontaneous corrosion phenomena while cumulative methods such as weight loss and hydrogen collection can only affords corrosion rate data after a certain period of immersion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In generation/collection (G/C) mode of SECM, electrochemically oxidisable or reducible species produced at the substrate can be sensed via an electrochemical reaction at the SECM probe. Applying an oxidative potential at the SECM, flux of H 2 evolution can be sensed and implemented to evaluate corrosion behaviour on Mg surface with a localized approach [13][14][15]. In comparison to other well-trusted corrosion measurement methods such as weight loss measurement and hydrogen collection [16,17], SECM presents the unique capability of studying spontaneous corrosion phenomena while cumulative methods such as weight loss and hydrogen collection can only affords corrosion rate data after a certain period of immersion.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies of cytotoxicity of REs on primary human and mouse cells demonstrated highest relative cytotoxicity of La and Ce while good cell viability was achieved in presence of Eu, Nd and Pr [27]. A recently advanced [13,15] electrochemical approach using SECM was used to evaluate H 2 evolution as a measure of corrosion protection afforded by the surface treatment. Degradation of the Pr conversion layer on AZNd is also studied at a local scale using SECM in AC mode.…”
Section: Introductionmentioning
confidence: 99%
“…In a study targeting the use of Mg alloys as biodegradable implants, Jamali et al employed an aqueous buffer to characterize the corrosion using FcMeOH and control the rate of H 2 evolution. 9 Our group recently reported the use of non-aqueous media (ethylene glycol) in combination with FcMeOH to investigate Mg alloy surface reactivity for automotive applications, limiting H 2 evolution severely. 23 Moreover, the use of arsenic as a cathodic poison 24 or a decreased concentration of NaCl electrolyte solution 9,15 are also avenues that have succeeded in decreasing H 2 evolution.…”
mentioning
confidence: 99%
“…1,2 In corrosion science, the generation-collection, feedback and potentiometric modes were used to characterize 3 or initiate 4 pitting corrosion, probe a precise ion of interest [5][6][7] , and quantify surface reactivity of heterogeneous materials 8 . The feedback mode [9][10][11][12] , which relies on the addition of a redox mediator in the corroding solution 13,14 and substrate-generation/tip-collection 9,15 mode, through the directed detection of evolved H 2 evolution 16,17 have been used to quantify the localized heterogeneous reactivity of corroding Mg alloys.…”
mentioning
confidence: 99%
See 1 more Smart Citation